2013
DOI: 10.1016/j.jaci.2013.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Joint modeling of parentally reported and physician-confirmed wheeze identifies children with persistent troublesome wheezing

Abstract: We identified a novel group of children with persistent troublesome wheezing, who have markedly different outcomes compared with persistent wheezers with controlled disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
118
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 35 publications
13
118
3
Order By: Relevance
“…Lung function was progressively worse with the increasing number of exacerbations and hospital admissions. This is consistent with the results of our recent study in which children with persistent troublesome wheeze (defined using latent class analysis on both parental and primary-care reports of wheeze, and characterized by frequent exacerbations) had significantly greater increase in sRaw over time compared with persistent wheezers with controlled disease (27). Similar to the findings on wheeze phenotypes, our data demonstrate that it is not just atopy, but a specific atopy phenotype that is associated with poor lung function (multiple early atopy, comprising approximately one-quarter of children conventionally defined as being atopic [30]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lung function was progressively worse with the increasing number of exacerbations and hospital admissions. This is consistent with the results of our recent study in which children with persistent troublesome wheeze (defined using latent class analysis on both parental and primary-care reports of wheeze, and characterized by frequent exacerbations) had significantly greater increase in sRaw over time compared with persistent wheezers with controlled disease (27). Similar to the findings on wheeze phenotypes, our data demonstrate that it is not just atopy, but a specific atopy phenotype that is associated with poor lung function (multiple early atopy, comprising approximately one-quarter of children conventionally defined as being atopic [30]).…”
Section: Discussionsupporting
confidence: 92%
“…We extracted all data from primary care medical records, including wheeze episodes, prescriptions of asthma medications, oral corticosteroid prescriptions, emergency department admissions, and asthma-and wheeze-related hospitalizations (27).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The present study would suggest that asthma is secondary to atopy in these children. Other studies have also shown a strong association between atopy and asthma persistence, as reflected by the atopic asthma group in the present study [5,14]. Nonatopic asthma has resulted as a separate entity in some previous analyses [7,9,12].…”
supporting
confidence: 71%
“…wheeze", "early transient wheeze" or "late onset wheeze" [3][4][5][6]. Similarly we investigated symptoms of cough and wheeze at two time-points in the Leicestershire cohort studies and identified patterns such as "transient viral wheeze" and "atopic persistent wheeze" [7,8].…”
mentioning
confidence: 99%
“…Recent developments in machine learning (a data‐driven approach to identify structure within the data using unsupervised learning of latent variables) provide new ways to capture the heterogeneity in patterns of responses to multiple items. Machine learning is increasingly used to disaggregate complex phenotypes in respiratory medicine and allergy 8, 9, 10, 11, 12, 13, 14, 15, where conventional modelling techniques might not uncover the underlying complexity 16.…”
Section: Introductionmentioning
confidence: 99%